2017
DOI: 10.1007/s10511-017-9499-0
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Kinematics Derived From Data in the RAVE5, UCAC4, PPMXL, and Gaia TGAS Catalogs

Abstract: The spatial velocities of the stars with high-precision positions, proper motions and parallaxes from the Gaia TGAS catalog and line-of-sight velocities from the RAVE5 catalog are considered. From the sample of 92395 stars with the age estimates we have obtained the following kinematic parameters: (U, V, W ) = (9.42, 20.34, 7.21) ± (0.12, 0.10, 0.09) km s −1 , Ω = 26.29 ± 0.39 km s −1 kpc −1 and Ω ′ = −3.89 ± 0.08 km s −1 kpc −2 , where V 0 = 210 ± 6 km s −1 (for adopted R 0 = 8.0 ± 0.2 kpc), and the Oort cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Note that Bobylev and Bajkova (2017) found p = 0.96 from the kinematics of distant OB stars. Having analyzed the line-of-sight velocities and proper motions of more nearby red giants from the RAVE5 catalogue, Vityazev et al (2017) found this correction factor to be 0.96, but its value from main-sequence dwarfs was 0.72.…”
Section: Resultsmentioning
confidence: 99%
“…Note that Bobylev and Bajkova (2017) found p = 0.96 from the kinematics of distant OB stars. Having analyzed the line-of-sight velocities and proper motions of more nearby red giants from the RAVE5 catalogue, Vityazev et al (2017) found this correction factor to be 0.96, but its value from main-sequence dwarfs was 0.72.…”
Section: Resultsmentioning
confidence: 99%
“…For some of the stars (TGAS, Tycho-Gaia Astrometric Solution) their proper motions were determined with a mean epoch difference of about 24 years with a mean error of about 0.06 mas yr −1 for the stars common to the Hipparcos catalogue (1997) and ∼mas yr −1 for the remaining stars . Using these data, various authors performed a number of important studies devoted to the kinematics of stars from the solar neighborhood (Bovy 2017;Hunt et al 2017; Bobylev and Bajkova 2017; Vityazev et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The signs of the unknowns were chosen so that rotations from the x axis to the y axis, from y to z, and from z to x are positive. Thus, the angular velocity of the Galactic rotation will be negative here, in contrast to many other studies in which the Galactic rotation was taken to be positive, for convenience [27][28][29].…”
Section: Galactic Rotation Parametersmentioning
confidence: 85%